2018
DOI: 10.21037/jtd.2018.01.153
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing radiation dose and fractionation for the definitive treatment of locally advanced non-small cell lung cancer

Abstract: Radiation therapy is the foundation for treatment of locally advanced non-small cell lung cancer (NSCLC), a disease that is often inoperable and has limited long term survival. Local control of disease is strongly linked to patient survival and continues to be problematic despite continued attempts at changing the dose and fractionation of radiation delivered. Technological advancements such as 4-dimensional computed tomography (CT) based planning, positron emission tomography (PET) based target delineation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…In this study, the median dose administered over the tumor was 83 Gy x 30 fractions and most patients received CT concurrently. Local control at two years was 82% and OS 25 months 30 .…”
Section: A H E a D O F P R I N Tmentioning
confidence: 93%
“…In this study, the median dose administered over the tumor was 83 Gy x 30 fractions and most patients received CT concurrently. Local control at two years was 82% and OS 25 months 30 .…”
Section: A H E a D O F P R I N Tmentioning
confidence: 93%
“…Multiple studies have demonstrated such an approach to be safe and effective. [38][39][40] Shorter courses have been associated with decreased immunosuppression in other cancers such as leukemia and pancreatic cancer. [41][42][43] This may offer advantages for LA-NSCLC, although minimizing the number of visits may provide the most risk reduction.…”
Section: Non-operative Managementmentioning
confidence: 99%
“…Nevertheless, a further improvement of survival by both better local and systemic control remains challenging . Better LC and OS by cCRT go hand in hand with potentially higher toxicity, which is one of the reasons why not all patients may be regarded as fit enough for the concurrent approach by the treating physician . The second reason are comorbid conditions, which allow for the inclusion of only 30% of the patient population with stage III NSCLC in concomitant treatment regimens .…”
Section: Introductionmentioning
confidence: 99%
“…The second reason are comorbid conditions, which allow for the inclusion of only 30% of the patient population with stage III NSCLC in concomitant treatment regimens . While guidelines generally propose concurrent treatment some of them, such as The National Institute for Health and Care Excellence (NICE), recommend alternative fractionation schedules (eg, CHART) for patients who are not eligible for the concurrent approach …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation